New Viewpoint Era of Weather Monitoring: Arduino Based Portable Weather Station Design - Suryawijaya, Tito; Ingsih, Kusni; Laurent, Fischella Andrew (Jurnal Inovasi Teknologi, 2023)
Weather changes play a crucial role in key sectors in Indonesia, such as agriculture and fisheries. However, limited weather data in all regions is an obstacle. This research proposes an innovative Arduino-based weather monitoring instrument that is flexible, economical and increases data availability in Indonesia. The ergonomic and flexible design of the Portable Weather Station allows mobility without dependence on building structures. With real-time monitoring using sensors for temperature, humidity, air pressure, wind speed and wind direction, this tool provides comprehensive information. Field testing shows good operation. The diversity of sensor parameters and efficient design make the Portable Weather Station innovative. Optimizing energy use and integration of advanced technologies, such as remote monitoring and cloud data processing, are recommended. The benefits involve easy and accurate access to weather information, supporting vital sectors. With continuous monitoring and evaluation, the Portable Weather Station has the potential to be an effective solution in dynamic weather monitoring, advancing sectors such as agriculture, fisheries and environmental policy, and creating communities that are more resilient to climate and economic change.